Dosa sebagai Penyimpangan Gerak Cinta (Philautia) dan Respons Pedagogi Ilahi: Analisis Tematik Konsep Dosa Menurut St. Maximus Sang Pengaku Iman - Cicilia Sirileleu; Hendi Wijaya (JOURNAL of THEOLOGICAL STUDENTS, 2026)
This article analyzes St. Maximus the Confessor’s understanding of sin as a theological-anthropological reality and the divine response to it. Using qualitative thematic analysis of primary and secondary Patristic sources, this study identifies four main themes. First, the essence of sin as a deviation of love’s movement (philautia) from a theocentric to a distorted self-centered orientation. Second, the origin of sin in the misuse of gnomic will, which fails to align with the divine logos. Third, the consequences of sin as existential fragmentation, disintegration of human relations with God and others, and bondage to death. Fourth, God’s response through a therapeutic and transformative pedagogy of love. These findings reveal that for Maximus, sin is a relational crisis answered by God through divine education toward restoration and reunification with Him. This article enriches Patristic moral theology by affirming the relational, therapeutic, and pedagogical character of sin and salvation